PROGNOSIS OF PRIMARY NON-HODGKIN’S LYMPHOMAS OF THE ORGAN OF VISION - Ye. Ye. Grishina; I. V. Poddubnaya; E. S. Guzenko; E. G. Gemdzhyan (Опухоли головы и шеи, 2015)
Much attention has been recently given to the prognosis of extranodal non-Hodgkin’s lymphomas (NHL). All currently available prognostic scales fail to fully characterize the prognosis of primary NHL of the eye and its accessory apparatus.The purpose of this study was to identify prognostic factors for vision and life in patients with primary NHL of the organ of vision. Retrospective and prospective studies of the specific features of the disease in 94 patients with primary NHL of the organ of vision revealed some factors influencing its prognosis.